CORRELATION BETWEEN PERSENTTRANSMITANCE VALUE (%T) OF Fe-O WITH AGE OF HUMAN BLOODSTAIN ON COTTON CLOTH USING INFRA RED SPECTROPHOTOMETRY - Dede Rosady Gustaman; M. Tegar Indrayana; Fatmawati " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
In the case of violent crimes such as murder, assault and rape, it is possible to find biological fluids such as blood spots at the crime scene . Blood spots contained two components, such as cellular component consisting of erythrocytes, leukocytes, platelets and plasma components. Erythrocytes contained hemoglobin that contain iron atom (Fe). Iron atom in heme would be reduced from Fe2+ to Fe 3+ due to reaction with oxygen. Alteration of Fe2+ to Fe3+ can be analyze by using infrared spectrophotometric. This study aims to determine the change in the value of % T in human bloodstains on cotton cloth functional groups contained in the molecule Fe-O. This study is experimental. Samples were white cotton cloth soaked in human blood. To see the correlation of % T with the age of bloodstains on cotton cloth used Pearson correlation test. The results show that no correlation was found from persenttransmitance Fe-O with age human bloodstain on cotton cloth using infra red spectrophotometry.Keyword : Persenttransmitance Fe-O, bloodstain